The Influence Of Financial Ratios On Banking Stock Prices: Economic Growth As An Intervening Factor (2019-2023) - Agus Triwantoro; Bambang Ismanto; Destri Sambara Sitorus (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to examine the effect of financial ratios CR, DER, and NPM on the stock price of banking companies through economic growth as an intervening variable. The method used is quantitative with fixed effect panel data regression analysis to investigate the factors that influence banking stock prices. The sample is limited to state-owned banks that consistently present quarterly financial reports from 2019 to 2023. The results showed that DER and NPM have an effect on economic growth. Meanwhile, CR has no effect on economic growth. NPM ratio and economic growth affect the share price of state-owned banks. However, CR and DER have no effect on the share price of state-owned banks. NPM affects stock prices through the intervening variable of economic growth. Meanwhile, CR and DER have no effect on stock prices through the intervening variable of economic growth.